The Importance Of Community Welfare In Economic Growth Through Government Spending - Rokhman, Hasbiah (AIBPM Publisher, 2023)
Abstract: The aim of this research is to provide evidence of the effect of general allocation funds and special autonomy funds on economic growth by mediating community welfare. The type of research used in this research is quantitative research with a descriptive approach. The analysis and research was carried out using time series data for the years 2018-2021. And cross section data from 13 regencies/cities in West Papua Province. The results of this study found that the general allocation fund had a positive and significant effect on people's welfare; special autonomy funds have a positive and significant impact on the welfare of the community; general allocation funds have a positive and significant effect on economic growth; special autonomy funds have a positive and significant impact on the welfare of the community; community welfare has a positive and significant effect on economic growth; general allocation funds have a positive but not significant effect on economic growth through community welfare; special autonomy funds have a positive but not significant effect on economic growth through community welfare. Keywords: the general allocation fund, special autonomy funds, community welfare, economic growth